2020
DOI: 10.4314/ijbcs.v13i6.15
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation du tourteau de neem (<i>Azadirachta indica</i>) et de la micro-dose d’engrais minéraux pour la production du maïs en zone Sud-soudanienne du Burkina Faso

Abstract: RESUMELes sols du Burkina Faso sont caractérisés par leur pauvreté en éléments nutritifs et en matière organique. Plusieurs sources de matière organique ont été étudiées mais très peu d'études se sont intéressées à l'utilisation du tourteau de neem (Azadirachta indica). Un dispositif en blocs de Fisher complètement randomisé comprenant 7 traitements a été mis en place au cours des saisons humide 2017 et 2018. Les traitements sont les fumures T0 : Sans apport de fertilisants ; T1 : NPK+urée 200 kg/ha + 100 kg/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…When evaluating agronomic and climatic approaches to sorghum adaptation, the results obtained were indeed lower than those observed in our study (Salifou et al, 2018). Other studies also concluded that sorghum grain yields were higher (2293 kg.ha -1 ) with a high dose of 6 t.ha -1 of neem cake and a yield of 1783 kg.ha -1 with a dose of 2 t.ha -1 (Traore et al, 2021). These results are like those of the present study in which 6 t.ha -1 of compost and 150 kg.ha -1 of NPK were applied under rectangular zaï on the basis of volumetric calculations.…”
Section: Interactive Effect Of the Length Of Rectangular Zaï Pits Fer...contrasting
confidence: 93%
“…When evaluating agronomic and climatic approaches to sorghum adaptation, the results obtained were indeed lower than those observed in our study (Salifou et al, 2018). Other studies also concluded that sorghum grain yields were higher (2293 kg.ha -1 ) with a high dose of 6 t.ha -1 of neem cake and a yield of 1783 kg.ha -1 with a dose of 2 t.ha -1 (Traore et al, 2021). These results are like those of the present study in which 6 t.ha -1 of compost and 150 kg.ha -1 of NPK were applied under rectangular zaï on the basis of volumetric calculations.…”
Section: Interactive Effect Of the Length Of Rectangular Zaï Pits Fer...contrasting
confidence: 93%
“…La variété kapelga de sorgho (Sorghum bicolor (L.) Moench) utilisée a un rendement potentiel en grain de 2800 kg.ha -1 et de 1200 kg.ha -1 en milieu paysan (Traore et al, 2021). Les pailles servent aussi d'aliments bétail, de toitures et de palissages (Clavel et al, 2008).…”
Section: Matériel Végétal Et Caractéristiques Des Fertilisants Et Des...unclassified
“…The use of organic substrates for the restoration of soil production capacity has been demonstrated by many researchers (Habimana et al, 2014;Koulibaly et al, 2015;Olaiya et al, 2015;Gomgnimbou et al, 2019;Traoré et al, 2019;Tshala Upite et al, 2019). Blanchard et al (2014) showed that there was a diversity of organic substrates that are produced and used by the farmers in rural area.…”
Section: Introductionmentioning
confidence: 99%